2012
DOI: 10.1590/s1677-55382012000400002
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of prostate cancer in Brazil is higher in Black men than in White men: systematic review and meta-analysis

Abstract: INTRODUcTIONProstate cancer is the most common form of noncutaneous cancer in men and the second leading cause of male cancer mortality. The incidence of prostate cancer varies according to racial/ethnic differences in several countries (1). The estimated incidence of prosBackground: Black men have a higher incidence of prostate cancer compared with White men in several countries. In Brazil, most studies reported a similar prevalence of prostate cancer between Blacks and Whites as a result of the high race mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
1
14
0
7
Order By: Relevance
“…Non--Whites in Brazil includes an intermediate Brown (pardo) category along a white-to-black color continuum, often used as a proxy for mulattos or persons with White and Black admixture (14).…”
Section: Racementioning
confidence: 99%
See 1 more Smart Citation
“…Non--Whites in Brazil includes an intermediate Brown (pardo) category along a white-to-black color continuum, often used as a proxy for mulattos or persons with White and Black admixture (14).…”
Section: Racementioning
confidence: 99%
“…The prevalence of prostate cancer in Brazil is higher in Black men compared to White men (12)(13)(14)(15). We studied the influence of race in regard to biochemical recurrence after radical prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Although the risk of prostate cancer in the present study was not signifi cantly increased for black versus white men (adjusted RR 1.56, 95%CI 0.64-3.82), similarly to several other Brazilian studies (8-11), a meta-analysis evaluating the prevalence of prostate cancer in black versus white men in Brazil, including the results of our study, demonstrated that the pooled risk of prostate cancer was signifi cantly increased in blacks (RR 1.55, 95%CI 1.32-1.82), suggesting that race is a signifi cant risk factor for prostate cancer in Brazilian men, and that the individual results of most published studies may have been limited by a low sample, a reduced proportion of black men, or a small rate of prostate cancer in each study group (12).…”
Section: Discussionmentioning
confidence: 60%
“…O predomínio de homens portadores desta doença que se declararam brancos é semelhante a estudos brasileiros que identificaram também o predomínio de homens brancos (11,19) . Contudo, estes dados divergem das estatísticas mundiais, que apontam predominância em indivíduos da raça negra (1,20) . A baixa escolaridade identificada na população pesquisada não chama atenção, pois se trata de indivíduos predominantemente idosos, cujas famílias nas primeiras décadas do século passado, priorizavam a sobrevivência em detrimento da escolarização (12) .…”
Section: Discussionunclassified